2006
DOI: 10.1007/s10495-006-3978-9
|View full text |Cite
|
Sign up to set email alerts
|

Role of Src-specific phosphorylation site on focal adhesion kinase for senescence-associated apoptosis resistance

Abstract: A decreased apoptotic response toward noxious stress is an issuing characteristic of the aging phenotype. Hydrogen peroxide or staurosporine induced apoptosis readily in young cells but not in senescent cells. We showed that focal adhesion kinase (FAK) expression and its phosphorylation at Tyr397, autophosphorylation site for focal adhesion formation, and Tyr577, Src-dependent phosphorylation site, were both increased in senescent cells. Moreover, FAK was inactivated proteolytically by apoptotic stimuli in you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 38 publications
3
34
0
Order By: Relevance
“…This is in agreement with other studies that have reported a decrease in induced apoptosis in old cells in response to different stimuli, including oxidative stress (Higami and Shimokawa 2000;Lee and Wei 2007) and γ-rays (Polyak et al 1997). Likewise, previous studies have shown that senescent fibroblasts are resistant to apoptosis induced by UV light (Ryu et al 2006) oxygen radicals (Gansauge et al 1997), serum withdrawal, H 2 O 2 , staurosporine, and thapsigargin (Wang 1995;Ryu et al 2006Ryu et al , 2007. On the other hand, other studies have shown that aging enhances apoptosis triggered by various challenges (Higami and Shimokawa 2000;Lee and Wei 2007).…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with other studies that have reported a decrease in induced apoptosis in old cells in response to different stimuli, including oxidative stress (Higami and Shimokawa 2000;Lee and Wei 2007) and γ-rays (Polyak et al 1997). Likewise, previous studies have shown that senescent fibroblasts are resistant to apoptosis induced by UV light (Ryu et al 2006) oxygen radicals (Gansauge et al 1997), serum withdrawal, H 2 O 2 , staurosporine, and thapsigargin (Wang 1995;Ryu et al 2006Ryu et al , 2007. On the other hand, other studies have shown that aging enhances apoptosis triggered by various challenges (Higami and Shimokawa 2000;Lee and Wei 2007).…”
Section: Discussionsupporting
confidence: 93%
“…In a previous study, we found that caspase-3 and PARP cleavages did not occur in H 2 O 2 -induced apoptosis of both young and senescent HDFs. 1 Dysregulation of phospho-CREB in the senescent HDFs. CREB, a Bcl-2 transcription factor, plays a critical role in regulation of apoptosis in many cell types.…”
Section: Resultsmentioning
confidence: 99%
“…The senescent phenotype is characterized by an increase in cell size, a distinct flat and enlarged morphology, 1,2 appearance of senescence-associated b-galactosidase (SA-bgalactosidase) activity, 3 hypo-responsiveness to growth factors, 4 resistance to apoptosis caused by stimuli such as UV, H 2 O 2 , staurosporine, etoposide and ceramide, 1,5,6 and broad changes in gene expression. 7 The mechanisms conferring resistance to stress-induced apoptosis in senescent human diploid fibroblasts have not been well studied.…”
mentioning
confidence: 99%
“…Silencing FAK expression with small interfering RNAs resulted in decreased migration of lung cancer cells (28) and glioblastoma cells (29). Finally FAK silencing has been shown to lead to apoptosis in human fibroblasts (30) and ovarian cancer cells (31).…”
mentioning
confidence: 99%